Traceable dynamic public auditing with identity privacy preserving for cloud storage - ZHANG, Yinghui (Institutional Knowledge at Singapore Management University, 2019)
In cloud computing era, an increasing number of resource-constrained users outsource their data to cloud servers. Due to the untrustworthiness of cloud servers, it is important to ensure the integrity of outsourced data. However, most of existing solutions still have challenging issues needing to be addressed, such as the identity privacy protection of users, the traceability of users, the supporting of dynamic user operations, and the publicity of auditing. In order to tackle these issues simultaneously, in this paper, we propose a traceable dynamic public auditing scheme with identity privacy preserving for cloud storage. In the proposed scheme, a single user, including a group manager, is unable to know the signer's identity. Furthermore, our scheme realizes traceability based on a secret sharing mechanism and supports dynamic user operations. Based on the security and efficiency analysis, it is shown that our scheme is secure and efficient.